Green organizational identity and sustainable innovation in the relationship between environmental regulation and business sustainability: Evidence from China's manufacturers. (July 2022) - Liu, Tiansen; Xing, Xinpeng; Song, Yazhi; Zhu, Yu; Zhu, Yue
Bridging government involvement and business sustainability, particularly in manufacturers, is becoming a new research interest. To enrich this knowledge area guided by the Institutional Theory, this study builds a multiple mediation model to investigate the effect of environmental regulation on business sustainability by concerning on the chain mediation effect of green organizational identity and sustainable exploration/exploitation innovations. China's manufacturers that are a key component of emerging markets have been analyzed by this study because of their significant impacts on climate change, substantial contributions to the boom of industries, and distinctive governance structures. By investigating China's manufacturers such as shipbuilding, energy, food, and daily necessities manufacturing sectors, we witness that the relationship between environmental regulation and business sustainability could be positively subsequently mediated by green organizational identity and sustainable innovation. While this identity does not exercise a positive mediation between environmental regulation and business sustainability significantly. Furthermore, both sustainable exploration/exploitation innovations exercise a significantly positive mediation between green organizational identity and business sustainability. We therefore conclude that manufacturers of emerging markets need a thoughtful deployment in pro-environmental psychologies and behaviors to closely bridge environmental regulation and business sustainability instead of only concerning on one aspect. This study has significant implications for emerging markets constructing a comprehensive as well as systematic pro-environmental path by using the merit of Institutional Theory to enhance business sustainability with more standardized and professional ways.